Environmental assessment in the process of applying lithographic inks Korien Group Company. - Castro Peláez, Lizet Jessica (2013)
Solvents and inks are chemical products more often used in the graphic arts industry. Some of these products can be extremely dangerous to the environment and human health. They can even cause death if used with no appropriate precautions. Prior knowledge of the associated risks while used and an effective safety and health system, are the best preventive protection for workers against these risks. The objective of this study is both to finding the contaminating products which generate strong pollution and to present real values of what happens during the printing process in a plant for the implementation of offset inks. It is also the purpose of this research to present analysis of volatile compounds, water and solid waste. A review of ink types and analysis of contaminants are also included. It is also possible to know the levels o contaminants in air emission analysis COV (volatile components), and analysis of liquid effluents and solid waste where the company has no control. Some results are explained and recommendations are also given.